THE EFFECT OF PRODUCT INNOVATION AND MARKET ORIENTATION ON SALES PERFORMANCE IN THE HOME INDUSTRY KERIPIK IN BIREUEN DISTRICT - Mulyadi Mulyadi; Koko Bustami; Imam Malik; Lakharis Inuzula (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
The purpose of this research is to know the effect of product innovation and market orientation on sales performance and impact to the productinnovation in the Home Industry Keripik in Bireuen District. The result of research should be use full in practical nor theoretical, that substance on marketing development management, the specific is entrepreneur ‘home industry Keripik Bireuendistrict to increase product innovation, market orientation and sales performance. The methods of research use Quantitative Research, with the nature descriptive research and verivicative. Data collecting through questioner with field study technique, the sampling census. The field data collecting is carry on 2021. The statistic analysis technique to test the hypothesis use analysis and sobel test. Basedon analysis result influence directly effect and not directly effect find that market orientation on product innovation have a positive influent and significant on sales performance in the Home product industry Keripik Bireuen District. Based on result mediation effect test results concluded that variable of innovation mediate on effect market orientation partial to sale performance Home industry Keripik Bireuen District. The mediate test result indicate all mediation.